BehaviorScope: Real-Time Remote Human Monitoring Using Sensor Networks - Lymberopoulos, Dimitrios; Bamis, Athanasios; Teixeira, Thiago; Savvides, Andreas (Information Processing in Sensor Networks; Proceedings: International Conference on Information Processing in Sensor Networks, 2008: St. Louis, MO, 2008)
In this demonstration we present the Behavior Scope, a system for interpreting human activity patterns using a sensor network and its application to elder monitoring in assisted living. The Behavior Scope provides a runtime,user-programmable framework that processes streams of timestamped sensor data along with prior context informationto infer activities and generate appropriate notifications. Human activities are described in high-levelscripts that are directly mapped to a hierarchy of probabilistic grammars that parse low-level sensor measurements into high-level distinguishable activities. Activities of interestare pre-programmed into a specification that is used by the system to interpret the incoming sensor data stream. The system interprets the activities to generate summaries andother triggered notifications that are propagated to stakeholders via email and cell-phone text messages.